2019
DOI: 10.1111/1471-0528.15665
|View full text |Cite
|
Sign up to set email alerts
|

Vaginoscopy Against Standard Treatment: a randomised controlled trial

Abstract: Objective To evaluate whether vaginoscopy or standard hysteroscopy was more successful in the outpatient setting. Design Randomised controlled multicentre trial. Setting Outpatient hysteroscopy clinics at two UK hospitals. Population 1597 women aged 16 or older undergoing an outpatient hysteroscopy. Methods Women were allocated to vaginoscopy or standard hysteroscopy using third party randomisation stratified by menopausal status with no blinding of participants or clinicians. Main outcome measures The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 17 publications
3
64
2
Order By: Relevance
“…After the initial title and abstract screening, the full‐texts of 100 potentially eligible citations were retrieved for evaluation. Finally, 39 RCT (Women n = 3964) were included in the present systematic review and NMA. Figure shows the PRISMA flowchart.…”
Section: Resultsmentioning
confidence: 99%
“…After the initial title and abstract screening, the full‐texts of 100 potentially eligible citations were retrieved for evaluation. Finally, 39 RCT (Women n = 3964) were included in the present systematic review and NMA. Figure shows the PRISMA flowchart.…”
Section: Resultsmentioning
confidence: 99%
“…In cases where the cervix is unable to be visualized with a speculum, use of o ce based vaginoscopy may provide a viable alternative for some procedures. 6 Vaginoscopy is typically performed with a rigid or exible hysteroscope, allowing visualization of the cervix and vagina, as well as the uterine cavity in many cases. Endometrial sampling via the hysteroscope is also feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of miniature hysteroscopes has facilitated this development. A randomised controlled multicentre trial in the UK concluded that vaginoscopy is quicker to perform, less painful, and more successful than standard hysteroscopy and therefore should be regarded as the technique of choice for outpatient hysteroscopy [7,8].…”
Section: Vaginoscopymentioning
confidence: 99%